Is the stingless bee Melipona quadrifasciata harmed by Bt toxins and glyphosate? - Seide, Vanessa Eler (2017)
Brazil is the second largest producer of genetically modified plants in the world and this agricultural practice expose native pollinators to contact and ingestion of Cry proteins, derived from the bacterium Bacillus thuringiensis (Bt). A transformation of maize and cotton varieties, with Bt gene transgenesis, causes a synthesis of Cry proteins in several plant tissues, especially in pollen, a source of protein for bees. Native bees may also be exposed to herbicides applied to crops, such as glyphosate. This compound can contaminate floral resources that are collected by foraging bees and taken to the interior of the colony. Cry and glyphosate proteins within the colony may be offered to the larvae in the form of food and this contamination can lead to immature malformation and death. Little is known about the effects of glyphosate and Cry proteins on stingless bees, especially when offered in the immature stage. We intend to test adverse effects of Cry1F and Cry2Aa and glyphosate herbicides on Melipona quadrifasciata (Apidae: Meliponini) larvae when mixed with food. The larvae were raised in laboratory and development and mortality were analyzed until the emergency period. After an emergency, bees were weighed and walking behavior was assessed. All larvae treated with glyphosate died a few days after the start of the experiments and the toxicity of this compound was higher than the imidacloprid insecticide, used as a positive control. Bees treated with Cry2Aa proteins survived longer and were delayed in development time when compared to bees from the negative control. Those treated with Cry1F protein also experienced developmental delay over the negative control. Walking behavior and body mass of the adult bees submitted to the different treatments were not affected. Therefore, Cry1F, Cry2Aa and glyphosate were toxic to M. quadrifasciata, causing lethal or sublethal effects that can damage the colony and reduce pollination activity.